Translation and validation of the Chinese version of EORTC QLQ-SWB32 assessing the spiritual wellbeing of women with gynecological cancer - Yue Feng; Jiangshan Luo; Tangwei Lin; Xingcan Liu; Xiujing Guo; Jing Chen; Bella Vivat (PLoS ONE, 2025)
Background This study aimed to translate the internationally developed and validated European Organization for Research and Treatment of Cancer measure of spiritual wellbeing (EORTC QLQ-SWB32) into Chinese, validate the translation with women with gynecological cancer, and examine associations between demographic variables and the scales of the measure. Methods The study followed EORTC translation guidelines. After pilot testing with sixteen gynecological cancer patients, we validated the final measure with another 200 patients. We analyzed reliability using Cronbach’s alpha coefficients. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and exploratory graphic analysis (EGA) were used to analyze the construct validity. A multiple linear regression model analyzed the relationship of the factors to spiritual well-being. Results Cronbach’s alpha coefficients showed good reliability, ranging from 0.885 to 0.907 in each dimension. The EFA (KMO = 0.876, χ2 = 2865.036, df = 231, P < 0.001) and EGA produced a four-dimension structure. CFA fit statistics indicated adequate fit to a four-dimension solution (χ2/df = 2.178, RMESA = 0.077, GFI = 0.973, SRMR = 0.057, CFI = 0.915, TLI = 0.902), which matched the dimensions and constituent items from the original measure. Regression analysis indicated that higher education levels correlated with higher scores on the Relationships with Others (RO) and Existential (EX) scales; unemployment with lower Relationship with Self (RS) scores, and lower incomes with lower EX scores; patients with religious beliefs scored higher on Relationship with God (RG). Conclusions The Chinese EORTC QLQ-SWB32 exhibits good reliability and validity among gynecological cancer patients, with dimensions aligning with those found in the original validation. This approved, validated instrument is now available for Chinese medical staff to use to assess the spiritual wellbeing of Chinese cancer patients and help improve understanding of the relevance of spiritual wellbeing to people from Chinese cultural backgrounds.